The Concept of Education by K.H. Ahmad Hasyim Muzadi - Fathinisthofa, Ais; Munawaroh, Ananda Alisya Qotrunnada; Nurwahidin, Nurwahidin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Education is an essential pillar for societal and national progress. In Indonesia, various strategies and methods have been developed to advance education, aiming to achieve greater welfare and development. This article aims to examine the concept of education according to K.H. Ahmad Hasyim Muzadi, a national and religious figure in Indonesia who once led the largest Muslim organization in the world, Nahdlatul Ulama. This research employs a library research method or thought study. The primary data for this study consists of K.H. Ahmad Hasyim Muzadi's speeches and written works found in books and journals. The secondary data is gathered from interviews with the family of K.H. Ahmad Hasyim Muzadi and books about his biography and testimonies. The collected data is then analyzed and elaborated to identify the key points regarding education according to K.H. Ahmad Hasyim Muzadi.